COACHING CLINIC ONLINE: PELATIHAN METODE PENELITIAN DAN PENGGUNAAN MENDELEY - Rini Adriani Auliana; Suparlan Suparlan; Yelli Fitri; Reny Wardiningsih; Herawati Khotmi; Eva Solina (CV Sentra Nusa Connection, 2025)
This online coaching clinic aims to provide knowledge about research methodology and research proposal preparation as well as how to use Mendeley to accounting students of Universitas Terbuka. This coaching clinic was conducted online through the MS Teams application platform, with a total of 15 participants and attended by 11 people from the Accounting Department of Universitas Terbuka from regions throughout Indonesia. This activity was held on Thursday, November 4, 2025 from 7:30 PM - 9:30 PM WIB for 120 minutes. The results of this activity are providing an understanding of research methods and the use of Mendeley to help Universitas Terbuka students prepare research proposals and research articles. The impact of this activity was felt by the student participants in the training in the form of an increase in their understanding and ability to create research proposals with appropriate research methods and the application of Mendeley to create research citations.